Highly selective production of succinic acid by metabolically engineered Mannheimia succiniciproducens and its efficient purification. Issue 10 (29th April 2016) - Choi, Sol; Song, Hyohak; Lim, Sung Won; Kim, Tae Yong; Ahn, Jung Ho; Lee, Jeong Wook; Lee, Moon‐Hee; Lee, Sang Yup
ABSTRACT: Succinic acid (SA) is one of the fermentative products of anaerobic metabolism, and an important industrial chemical that has been much studied for its bio‐based production. The key to the economically viable bio‐based SA production is to develop an SA producer capable of producing SA with high yield and productivity without byproducts. Mannheimia succiniciproducens is a capnophilic rumen bacterium capable of efficiently producing SA. In this study, in silico genome‐scale metabolic simulations were performed to identify gene targets to be engineered, and the PALK strain (Δ ldhA and Δ pta‐ackA ) was constructed. Fed‐batch culture of PALK on glucose and glycerol as carbon sources resulted in the production of 66.14 g/L of SA with the yield and overall productivity of 1.34 mol/mol glucose equivalent and 3.39 g/L/h, respectively. SA production could be further increased to 90.68 g/L with the yield and overall productivity of 1.15 mol/mol glucose equivalent and 3.49 g/L/h, respectively, by utilizing a mixture of magnesium hydroxide and ammonia solution as a pH controlling solution. Furthermore, formation of byproducts was drastically reduced, resulting in almost homo‐fermentative SA production. This allowed the recovery and purification of SA to a high purity (99.997%) with a high recovery yield (74.65%) through simple downstream processes composed of decolorization, vacuum distillation, and crystallization. The SA producer and processes developed in this study will allow economical production of SA in an industrial‐scale. Biotechnol. Bioeng. 2016;113: 2168–2177. © 2016 Wiley Periodicals, Inc. Abstract : Mannheimia succiniciproducens PALK strain (Δ ldhA, Δ pta‐ackA ) was constructed based on constraint‐based flux analysis to produce nearly homo‐succinic acid with a productivity high enough for economic industrial bio‐based succinic acid production.